Aplikasi E-Health Kesehatan Ibu dan Anak (KIA) Sebagai Inovasi Kota Cerdas - Ayu Dusea Widyadara1, Made; - Universitas Nusantara PGRI Kediri, Mochamad Bilal (IJNS - Indonesian Journal on Networking and Security, 2019)
Abstract - Until now the management of data on maternal and child health services (MCH) includes recording new patient registrations, recording patient visits and examinations, recording medical records, recording patient referral letters, and MCH service reports still carried out using cohort books. Whereas for MCH participants the data is stored in the MCH book which is a combination of maternal and child health cards, starting from the Towards Healthy Card (KMS) for pregnant women, KMS for toddlers, Family Planning Cards, child development cards, etc. As a result, medical data duplication often occurs such as re-recording with the same patient so that the medical history cannot be continuous, errors in recording, as well as in the process of searching and making reports takes a long time. The use of information technology can increase effectiveness and efficiency in a process of activities so that more quickly achieved. To solve problems that occur to date requires a web-based KIA e-Health application technology that is equipped with a system that records patient data, patient medical records, and KIA service reports as well as applications that are equipped with SMS, Whatsapp and or email broadcast features to remind patients MCH about the schedule of participant return visits, as well as immunization and vitamin delivery schedules for infants and toddlers by sending messages. With the development of the E-health application for Maternal and Child Health (MCH), the MCH data at the puskesmas will be more quality, integrated, and easier in making reports. Provision of immunization and vitamins for children and toddlers is more controlled. As well as creating uniformity in processing information and data at the online health center, so that it is integrated with health service units and cloud computing-based UPTD. Keywords: Maternal and Child Health, Puskesmas, e-Health, Cloud Computing Abstrak – Sampai saat ini pengelolaan data pelayanan Kesehatan Ibu dan Anak (KIA) meliputi pencatatan pendaftaran pasien baru, pencatatan kunjungan dan pemeriksaan pasien, pencatatan rekam medis, pencatatan surat rujukan pasien, dan laporan pelayanan KIA masih dilakukan dengan menggunakan buku kohort. Sedangkan pada peserta KIA data disimpan dalam buku KIA yang merupakan gabungan kartu-kartu kesehatan Ibu dan Anak, dimulai dari Kartu Menuju Sehat (KMS) ibu hamil, KMS balita, Kartu Keluarga Berencana, Kartu perkembangan anak, dll. Akibatnya sering terjadi duplikasi data medis seperti pencatatan ulang dengan pasien yang sama sehingga riwayat medis tidak bisa berkesinambungan, kesalahan dalam pencatatan, serta pada proses pencarian dan pembuatan laporan membutuhkan waktu lama. Penggunaan teknologi informasi dapat meningkatkan efektivitas dan efisiensi dalam sebuah proses kegiatan agar lebih cepat dicapai. Untuk memecahkan permasalahan yang terjadi sampai saat ini dibutuhkan teknologi aplikasi e-Health KIA berbasis web yang dilengkapi dengan sistem yang mencatat data pasien, rekam medis pasien, dan laporan pelayanan KIA serta aplikasi yang dilengkapi dengan fitur SMS, Whatsapp dan atau email broadcast untuk mengingatkan pasien KIA tentang jadwal kunjungan ulang peserta, serta jadwal imunisasi dan pemberian vitamin untuk bayi dan balita dengan mengirimkan pesan. Dengan dibangunnya aplikasi E-health Kesehatan Ibu dan Anak (KIA), maka data KIA pada puskesmas menjadi lebih berkualitas, terintegrasi, dan lebih mudah dalam pembuatan laporan. Pemberian imunisasi dan vitamin kepada anak dan balita lebih terkendali. Serta tercipta keseragaman dalam pengolahan informasi dan data puskemas secara online, sehingga terintegrasi dengan unit-unit pelayanan kesehatan dan UPTD berbasis cloud computing. Kata kunci: Kesehatan Ibu dan Anak, Puskesmas, e-Health, Cloud Computing